Thoughts on Nationalism Among Leaders of the Islamic Party of Malaysia (PAS) From 1951 to 2013: An Analysis Within PAS Framework - Abdul Manan, Nor Azizuddin; Abdullah, Muhammad Ainuddin Iskandar Lee; Sharifuddin, Mohd Dino Khairri (Online Journal of Research in Islamic Studies, 2024)
This study comprehensively examines the ideological perspectives on nationalism among the Pan-Malaysian Islamic Party (PAS) leaders from 1951 to 2013. The research addresses the divergence of views on nationalism within PAS, focusing on tops prominent leaders, and evaluates how these differences have shaped the party's direction. It explores the factors contributing to these ideological disparities and their implications for PAS's political future trajectory. Employing a single-method qualitative approach, this study utilizes library research, documentation analysis, and historical contextualization as its primary techniques. The PAS Presidential Speech Policy delivered at the Annual Muktamar is the primary source, complemented by secondary documents. The findings reveal significant ideological divisions within PAS regarding nationalism. While some leaders categorically reject nationalism as incompatible with Islamic principles, others conditionally accept it within an Islamic framework. These differing stances have influenced PAS leadership's ability to unify its members under a cohesive nationalistic ideology aligned with Islam. This study underscores how these ideological tensions have shaped PAS's policies and strategies. It offers insights into the party's evolving role in Malaysian politics and its broader implications for Islamic political movements.